Perspective: Consideration of Values When Setting Priorities in Nutrition Research: Guidance for Transparency. Issue 6 (10th September 2018) - Hawwash, Dana; Pinxten, Wim; Bonn, Noémie Aubert; Verstraeten, Roosmarijn; Kolsteren, Patrick; Lachat, Carl
ABSTRACT: Nutrition research can guide interventions to tackle the burden of diet-related diseases. Setting priorities in nutrition research, however, requires the engagement of various stakeholders with diverse insights. Consideration of what matters most in research from a scientific, social, and ethical perspective is therefore not an automatic process. Systematic ways to explicitly define and consider relevant values are largely lacking. Here, we review existing nutrition research priority-setting exercises, analyze how values are reported, and provide guidance for transparent consideration of values while setting priorities in nutrition research. Of the 27 ( n = 22 peer-reviewed manuscripts and 5 grey literature documents) studies reviewed, 40.7% used a combination of different methods, 59.3% described the represented stakeholders, and 49.1% reported on follow-up activities. All priority-setting exercises were led by research groups based in high-income countries. Via an iterative qualitative content analysis, reported values were identified ( n = 22 manuscripts). Three clusters of values (i.e., those related to impact, feasibility, and accountability) were identified. These values were organized in a tool to help those involved in setting research priorities systematically consider and report values. The tool was finalized through an online consultation with 7 international stakeholders. The value-oriented tool for priority setting in nutrition research identifies and presents values that are already implicitly and explicitly represented in priority-setting exercises. It provides guidance to enable explicit deliberation on research priorities from an ethical perspective. In addition, it can serve as a reporting tool to document how value-laden choices are made during priority setting and help foster the accountability of stakeholders involved.